Evaluation of quality status and detection of adulterants in selected commercial pickles and chutneys based on consumer attitude and laboratory analysis (Journal of the Bangladesh Agricultural University, 2014)
Quality of selected commercial pickles and chutneys were evaluated by conducting a baseline survey on the consumer attitude towards the products and analyzing the selected products for adulterants and performing sensory evaluation. The pickle and chutney samples were analyzed in selected accredited laboratories for the physicochemical parameters such as fluid portion percent by mass of the net mass, acidity as citric acid (% mg/gm), sodium benzoate (mg/Kg), arsenic (mg/Kg), Lead (mg/Kg), copper (mg/Kg), zinc (mg/Kg), tin (mg/Kg). The result showed that all the commercial samples have fluid portion within the BSTI range except samples D and E and all the heavy metals were below the detection level. In case of samples A and B acidity was lower than the optimum value. However, preservative used in the samples are much higher than that of accepted level. From the sensory and organoleptic evaluation it was found that the average scores obtained by the pickles and chutney products for colour & texture, taste & flavor, absence of defects and total scores were satisfactory in comparison to BSTI standard. Concerning to total energy content mango pickles sample A has greater energy content than sample B. Among chutneys sample C has greater energy content where sugar is the main source of energy. In conclusion, commercial pickle and chutney may be recommended as safe and fit for consumption as the values for quality and sensory parameters comply with the BSTI standards. The current views of consumers about the quality of commercial pickle and chutney obtained from the baseline survey has been proved wrong after comparing analyzed values with those standards. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21413 J. Bangladesh Agril. Univ. 12(1): 203-209, June 2014